2019
DOI: 10.1016/j.hrthm.2019.05.032
|View full text |Cite
|
Sign up to set email alerts
|

Voltage during atrial fibrillation is superior to voltage during sinus rhythm in localizing areas of delayed enhancement on magnetic resonance imaging: An assessment of the posterior left atrium in patients with persistent atrial fibrillation

Abstract: Background Bipolar electrogram voltage during sinus rhythm (V SR ) has been used as a surrogate for atrial fibrosis in guiding catheter ablation of persistent atrial fibrillation (AF), but the fixed rate and wavefront characteristics present during sinus rhythm may not accurately reflect underlying functional vulnerabilities responsible for AF maintenance. Objective The purpose of this study was determine whether, given adequate temporal sampl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
49
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 52 publications
(52 citation statements)
references
References 27 publications
2
49
0
Order By: Relevance
“…In our study the mean voltages recorded throughout the LA were lower during AF than SR which is in keeping with a recent study in which the voltage recorded during AF demonstrated a better correlation than SR when compared with a DE-MRI of the posterior wall of the LA. [5] This study also demonstrated that AF voltage recordings tend to stabilize after a period of 4 seconds. For the first time we have found a linear correlation between the voltage amplitude in SR and AF with adequate temporal sampling in the most common locations for substrate.…”
Section: Methods and Resultssupporting
confidence: 54%
“…In our study the mean voltages recorded throughout the LA were lower during AF than SR which is in keeping with a recent study in which the voltage recorded during AF demonstrated a better correlation than SR when compared with a DE-MRI of the posterior wall of the LA. [5] This study also demonstrated that AF voltage recordings tend to stabilize after a period of 4 seconds. For the first time we have found a linear correlation between the voltage amplitude in SR and AF with adequate temporal sampling in the most common locations for substrate.…”
Section: Methods and Resultssupporting
confidence: 54%
“…Kalman et al [14] reported that, in patients with PsAF, variation in rate and directionality of the wave front produces both general and regional changes in voltage, conduction velocity, and complex fractionation, resulting in significant changes in the BVM. Lim, et al [15] described that the correlation between LVA and MRI-DE in the LA is significantly improved when acquired during PsAF vs SR. More specifically, they reported that, with adequate sampling, mean PsAF voltage is a reproducible marker reflecting the functional response to the underlying PsAF substrate. This represents a limitation of our study.…”
Section: Bipolar Amplitude Mapsmentioning
confidence: 99%
“…Coronary microvascular dysfunction is exceptionally common in HFpEF and, when present, is associated with a two‐fold increase in the prevalence of AF . Cardiac magnetic resonance imaging (MRI) reveals meaningful myocardial fibrosis (in the LA and LV) in both patients with HFpEF and those with AF . Fibrosis is indicative of an underlying atrial and ventricular myopathy and may precede the clinical identification of AF or HFpEF …”
Section: Pathophysiological Mechanisms Leading To Hfpefmentioning
confidence: 99%
“…29,30 Cardiac magnetic resonance imaging (MRI) reveals meaningful myocardial fibrosis (in the LA and LV) in both patients with HFpEF 31-36 and those with AF. 37,38 Fibrosis is indicative of an underlying atrial and ventricular myopathy and may precede the clinical identification of AF or HFpEF. 32,39,40…”
Section: Pathophysiological Mechanisms Leading To Hfpefmentioning
confidence: 99%